Cyberbullying: A new kind of peer bullying through online technology and its relationship with aggression and social anxiety - İçellioğlu, Serra; YILDIRIM, MELİS SERAY ÖZDEN (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2014)
Cyberbullying is becoming a crucial problem that has been arised with increased use of internet and other technological devices. According to recent research in Turkiye %56 of 1470 internet users with avarege age 23, has indicated they become victims of cyberbullying at least once in their lifetime. The results have shown that the issue of cyberbullying should be considered as a problem that should be investigated. In this study, cyberbullying scale had been given to the university students aged between 18-29. Also, Spielberger's Trait Anger&Anger Styles Scale and Liebowitz Social Anxiety Scale had been given to examine the relationship between cyberbullying and aggression and social anxiety. Social anxiety and avoidance scores were significantly different between genders. The correlations between 10 indexes of cyberbullying behaviors and social anxiety scores together with anger (trait anger, anger-in, anger-out and anger control) scores were analyzed. Correlations were found between sending rude, vulgar or threating messages and anger-in scores, creating fake profile or web page statement and social anxiety, social avoidance, trait-anger and anger-out scores respectively, publishing photographs or videos of someone without consent and anger-in scores, sending online request for sexual relation statement and anger-out and anger control scores, hacking someone's web profile statement and anger-out and anger control scores, publishing fake statues or check-in notifications and anger-in and anger-out scores. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: Cyberbullying; Cybervictimization; Personality